Analysis of the modifying effects of TAP 1/2 genes on cystic fibrosis phenotype - Özbaş-Gerçeker, Filiz; Özçelik, Uğur; Kiper, Nural; Anadol, Deniz; Göçmen, Ayhan; Yılmaz, Engin; Erdem Yurter, Hayat; Özgüç, Meral (The Turkish Journal of Pediatrics, 2002)
Phenotypic variability has been reported in cystic fibrosis (CF) patients. TAP1 and TAP2 genes are encoding "the transporter associated with antigen processing" proteins. The aim of the present study was to analyze the frequency of TAP 1/2 variants in the Turkish population and to investigate a possible modifying role of these variants in CF phenotype. Sixty-three CF patients of known genotypes and 100 healthy control subjects were analyzed. There was a significant difference in the frequencies at positions 333 and 637 of TAP 1 gene and at position 665 of TAP 2 gene between patients and controls. Comparison of TAP gene polymorphisms in 36 CF patients homozygous for ΔF508 mutation with control subjects revealed a significant difference at position 665 of TAP 2 gene. These findings may be useful to assess the predisposition and to predict severity of the disease. We demonstrated that TAP genes might have modifying effects on the CF phenotype.
Keywords: cystic fibrosis; TAP 1/2 genes; modifying genes